(untitled) (Asia Pacific Journal of Social Innovation, 2024)
This paper dealt with the religious phenomenon of panaad in the province of Camiguin Island in Northern Mindanao. In tracing the meaning, development and purposes of panaad, the descriptive qualitative method has been employed. Part of the method are: in-depth reading of available texts related to the practice of pilgrimage, personal observation, and interview with selected pilgrims who had done the panaad during the Holy Week of 2011 and 2012. This research yielded the following findings: a) the meaning of panaad may vary on each pilgrim but it remains grounded on the religious practice of pilgrimage, which is a popular form of devotion among the Catholic faithful going back to the early Christians; b) the growth of panaad in Camiguin is facilitated by the initiative of the Catholic faithful who find the island an ideal place for pilgrimage during the Lenten season; c) the various purposes of panaad among the pilgrims can be drawn into two categories, namely: religious and personal. After 30 years, panaad in Camiguin has already taken root as an established spiritual devotion which, despite the dwindling numbers of pilgrims in the recent years, will continue to be practiced within the sacred time and sacred space of Camiguin island every Holy Week